Synthesis of Novel Dihydropyridothienopyrimidin-4,9-dione Derivatives - Kim, Youngjae; Kim, Minjoo; Park, Mooseong; Tae, Jinsung; Baek, Du-Jong; Park, Ki Duk; Choo, Hyunah (MDPI AG, 2015)
A novel molecular scaffold, dihydropyridothienopyrimidin-4,9-dione, was synthesized from benzylamine or p-methoxybenzylamine in six steps involving successive ring closure to form a fused ring system composed of dihydropyridone, thiophene and pyrimidone. The pharmacological versatility of the dihydropyridothenopyrimidin-4,9-dione scaffold was demonstrated by inhibitory activity against metabotropic glutamate receptor subtype 1 (mGluR1), which shows that the title compounds can serve as an interesting scaffold for the discovery of potential bioactive molecules for the treatment of human diseases.
Keywords: MGLUR1 ANTAGONISTS; CLOPIDOGREL; PAIN